THE APPLICATION OF E-VOTING IN GENERAL ELECTION: WILL IT BE POSSIBLE? - Widhiasthini, Ni Wayan (CosmoGov: Jurnal Ilmu Pemerintahan, 2022)
The goal of SDGs (Sustainable Development Goals) is to realize transparency and accountability of government performance, clean and accountable bureaucracy, and effective, efficient, and organized public services with good quality. E-voting has a strategic position in realizing the SDGs indicators, especially when looking at the potential of the KPU, ranging from the use of technology, human resources, and relationships with a wide range of stakeholders. This research uses a qualitative research design. Data were collected through in-depth interviews, documentation studies and observation. The research findings show that the SDGs indicators, especially in the field of governance and law, have been implemented by KPU through the practice of transparency, accountability of government performance, clean and accountable bureaucracy, effective and efficient public services, and quality through the optimal utilization of information technology. The practical implication is the recommendation to implement e-voting based on the results of the potential analysis conducted by KPU. The social interest arising from applying SDGs in the electoral field is the opening of optimal public participation space in the electoral stages. This research has successfully provided recommendations for the implementation of the General Election to be held in 2024.gb777